AS-SYEH ABDULLAH AL HARARY IDEAS ON ISLAMIC EDUCATION STUDIES - Muhammad Sirril Wafa (Al Ulya: Jurnal Pendidikan Islam, 2022)
This article tries to reveal the concept of Islamic education contained in the book of mukhtasor abdillah al-harari by as-sheikh abdullah al-harari which is one of the books that is masively studied in various institutions and islamic boarding schools in Indonesia. To reveal this, the researcher utilizes a research and review of literature and other library materials which are relevant to the problem being studied, which includes the materials contained in the book of mukhtasor abdillah al-harari as primary sources, and all articles related to Islamic education are secondary sources. Meanwhile, the data analysis technique was content analysis which was utilized to take conclusions through efforts to discover the characteristics of the message, and multiplied objectively and systematically. After the data is collected, then it is analyzed utilizing the scriptive method of data analysis.  The result show that: the first is the concept of Islamic education which includes; its meaning, its kinds, its principles, as well as the purpose of Islamic education itself. The second is Yang kedua yaitu Islamic education in the book of mukhtasor abdillah al-harari which includes matters that should be studied and carried out by every Muslim, such as prayer, fasting, zakat, haji and so on.